Horten's miraculous mechanisms - Evans, Lissa; Evans, Lissa (New York : Scholastic, 2012)
Ten-year-old Stuart is forced to move far away from all his friends. But on his very first day in his new home, Stuart is swept up in a quest to find his great-uncle Tony--a famous magician who literally disappeared off the face of the earth--and Tony's marvelous, long-lost workshop.
"Originally published in 2011 in Great Britain as Small change for Stuart"--T.p. verso.
6.1
3-6.
3-6
Keywords: Magicians -- Juvenile fiction; Missing persons -- Juvenile fiction; Fantasy; Magicians -- Fiction; Missing persons -- Fiction; Mystery and detective stories; Magicians -- Fiction; Missing persons -- Fiction; Mystery fiction; Fantastic fiction; Fantastic fiction; Mystery fiction